State Intervention in the Settlement of Interests Conflicts - Sturmthol, Adolf (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1958)
SummaryThe Author first describes the « contradictory values » which surround collective bargaining and industrial peace, going through a brief analysis of various industrial relations theories: those of Market, Government and Union Participation in Management. He then goes on to distinguish between various manifestations of industrial conflicts—one of which being the strike, which is not necessarily a symptom of « unhealthy » industrial relations. The Author states that government intervention in conflicts of interests must be the exception and must have their justification in each case. He founds his thesis on the on-the-spot study of numerous data collected from the United States, Great Britain, France, Germany and, Sweden.